“The Glorious American Banner Floating High above the Ramparts”: The Rise and Fall of Know-Nothingism in Wisconsin - Depew, Jennifer (Office of Student Research and Creative Activity, 2018)
Know-Nothingism was an anti-immigrant movement that gained prominence in the United States following a surge in Irish and German Catholic immigration during the 1840s and 1850s. Wisconsin, a new state with a diverse and fast-growing population, was uniquely poised to be a battleground for political fights between the native- and foreign-born. This paper recounts the efforts of Wisconsin Know-Nothings to vie with the Democratic and Republican parties for electoral supremacy from 1855 to 1857. Although not strong enough to run their own challengers in the 1855 gubernatorial election, the Know-Nothings contributed to an aura of frenzied paranoia about political purity that would result in one of the most notorious elections in the state’s history. In the 1856 presidential election, the Know-Nothings mounted a campaign that helped reveal cracks in the foundation of the Union and paved the way for the coming Civil War. The movement would ultimately divide over the issue of slavery, but during its brief ascendance, it ignited a furious, statewide debate over American values that impacted the formation of both major political parties.
Keywords: Know-Nothing Party; Xenophobia--Wisconsin; Nativism--Wisconsin